Integrating views on support for mid-level health worker performance: a concept mapping study with regional health system actors in rural Guatemala. Issue 1 (December 2015) - Hernández, Alison; Hurtig, Anna-Karin; Dahlblom, Kjerstin; San Sebastián, Miguel
Abstract Introduction Mid-level health workers are on the front-lines in underserved areas in many LMICs, and their performance is critical for improving the health of vulnerable populations. However, improving performance in low-resource settings is complex and highly dependent on the organizational context of local health systems. This study aims to examine the views of actors from different levels of a regional health system in Guatemala on actions to support the performance of auxiliary nurses, a cadre of mid-level health workers with a prominent role in public sector service delivery. A concept mapping study was carried out to develop an integrated view on organizational support and identify locally relevant strategies for strengthening performance. Methods A total of 93 regional and district managers, and primary and secondary care health workers participated in generating ideas on actions needed to support auxiliary nurses' performance. Ideas were consolidated into 30 action items, which were structured through sorting and rating exercises, involving a total of 135 of managers and health workers. Maps depicting participants' integrated views on domains of action and dynamics in sub-groups' interests were generated using a sequence of multivariate statistical analyses, and interpreted by regional managers. Results The combined input of health system actors provided a multi-faceted view of actions needed to support performance, which were organized in six domains, including:Communication and coordination, Tools to orient work, Organizational climate of support, Motivation through recognition, Professional development andSkills development . The nature of relationships across hierarchical levels was identified as a cross-cutting theme. Pattern matching and go-zone maps indicated directions for action based on areas of consensus and difference across sub-groups of actors. Conclusions This study indicates that auxiliary nurses' performance is interconnected with the performance of other health system actors who require support, including managers and community-level collaborators. Organizational climate is critical for making auxiliary nurses feel supported, and greater attention to improving the quality of hierarchical relationships is needed in LMIC settings. The participatory nature of the concept-mapping process enabled health system actors to collaborate in co-production of context-specific knowledge needed to guide efforts to strengthen performance in a vulnerable region.